Soil microbial abundance was more affected by soil depth than the altitude in peatlands - Zhao, Meiling; Wang, Ming; Zhao, Yantong; Hu, Nanlin; Qin, Lei; Ren, Zhibin; Wang, Guodong; Jiang, Ming (Frontiers in Microbiology, 2022)
Soil microbial abundance is a key factor to predict soil organic carbon dynamics in peatlands. However, little is known about the effects of altitude and soil depth and their interaction on soil microbial abundance in peatlands. In this study, we measured the microbial abundance and soil physicochemical properties at different soil depths (0–30 cm) in peatlands along an altitudinal gradient (from 200 to 1,500 m) on Changbai Mountain, China. The effect of soil depth on soil microbial abundance was stronger than the altitude. The total microbial abundance and different microbial groups showed the same trend along the soil depth and altitudinal gradients, respectively. Microbial abundance in soil layer of 5–10 cm was the highest and then decreased with soil depth; microbial abundance at the altitude of 500–800 m was the highest. Abiotic and biotic factors together drove the change in microbial abundance. Physical variables (soil water content and pH) and microbial co-occurrence network had negative effects on microbial abundance, and nutrient variables (total nitrogen and total phosphorus) had positive effects on microbial abundance. Our results demonstrated that soil depth had more effects on peatland microbial abundance than altitude. Soil environmental change with peat depth may lead to the microorganisms receiving more disturbances in future climate change.